Information Technologies in Biomedicine, Volume 3 - Piętka, Ewa.; Kawa, Jacek; Wieclawek, Wojciech; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
New computerized approaches to various problems have become critically important in healthcare. Computer assisted diagnosis has been extended towards a support of the clinical treatment. Mathematical information analysis, computer applications have become standard tools underpinning the current rapid progress with developing Computational Intelligence. A computerized support in the analysis of patient information and implementation of a computer aided diagnosis and treatment systems, increases the objectivity of the analysis and speeds up the response to pathological changes. This book presents a variety of state-of-the-art information technology and its applications to the networked environment to allow robust computerized approaches to be introduced throughout the healthcare enterprise. Image analysis and its application is the traditional part that deals with the problem of data processing, recognition and classification. Bioinformatics has become a dynamically developed field of computer assisted biological data analysis.   This book is a great reference tool for scientists who deal with problems of designing and implementing processing tools employed in systems that assist the radiologists and biologists in patient data analysis.  .
Keywords: Computational intelligence; Biomedical engineering; Health informatics; Artificial intelligence; Computational Intelligence; Biomedical Engineering and Bioengineering; Health Informatics; Health Informatics; Artificial Intelligence